The Myth of Universal Sensitive Responsiveness: Comment on Mesman et al. (2017). Issue 5 (23rd January 2018) - Keller, Heidi; Bard, Kim; Morelli, Gilda; Chaudhary, Nandita; Vicedo, Marga; Rosabal‐Coto, Mariano; Scheidecker, Gabriel; Murray, Marjorie; Gottlieb, Alma
Abstract : This article considers claims of Mesman et al. (2017) that sensitive responsiveness as defined by Ainsworth, while not uniformly expressed across cultural contexts, is universal. Evidence presented demonstrates that none of the components of sensitive responsiveness (i.e., which partner takes the lead, whose point of view is primary, and the turn‐taking structure of interactions) or warmth are universal. Mesman and colleagues' proposal that sensitive responsiveness is "providing for infant needs" is critiqued. Constructs concerning caregiver quality must be embedded within a nexus of cultural logic, including caregiving practices, based on ecologically valid childrearing values and beliefs. Sensitive responsiveness, as defined by Mesman and attachment theorists, is not universal. Attachment theory and cultural or cross‐cultural psychology are not built on common ground.